Sanksi bagi Penyelenggara Pinjaman Daring Legal yang Tidak Mematuhi Peraturan Otoritas Jasa Keuangan - Akobiarek, Suzette Hattingh; Pungus, Kristantika Renata; Kusuma, Rico Arden; Mulya, Christopher Alexius Alfa; Aprilia, Ivana (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
Legal online loan services (Pindar) are growing rapidly in Indonesia as an alternative financing solution that is easily accessible to the public. However, along with this growth, various violations have emerged by licensed operators, especially in billing practices that are not in accordance with the provisions of the Financial Services Authority (OJK). This research aims to analyze the regulations that must be complied with by legal pindar operators in accordance with POJK Number 40 of 2024 and examine the sanctions that can be imposed for violations of these regulations. The method used for this research are normative juridical with a statutory approach and a case approach. Data was obtained through literature studies from various regulations and legal literature. The results of the study show that the organizer is obliged to comply with the operational, administrative, and ethical billing provisions set by the OJK. In the event of a violation, the OJK can impose administrative sanctions, ranging from written warnings, freezing or restricting business activities, to the revocation of operational licenses. This research provides a theoretical contribution by clarifying the legal obligations of the organizer and adding to the legal literature regarding the supervision of the fintech lending sector. Practically, the results of this study are important for regulators in enforcing compliance and improving protection for the pindar service user community. The results of the study show that there are still rampant violations committed by the organizers, despite administrative sanctions given by the OJK, ranging from written warnings, freezing of business activities, fines, to revocation of operational permits. This shows that the strengthening of regulations has not been fully accompanied by the discipline of business actors in complying with the rules.